Integrated FRAM-FMEA based on PF-CRITIC and PF-WASPAS for Pandemic Disaster Risk Assessment - Can, Emine; Ayvaz, Berk; Tarakci, Emin (Contemporary Mathematics, 2025)
The utilization of trustworthy and optimistic risk evaluation methodologies is crucial in the continuously evolving context of global disasters and pandemics. This study has provided a summary of the suggested integrated methodology. The Functional Resonance Analysis Method (FRAM) and Failure Mode (FM) and Effect Analysis are combined in this article to present a novel hybrid approach that is further strengthened by the robustness of the Pythagorean Fuzzy-Criteria Importance Through Intercriteria Correlation (CRITIC) and Pythagorean Fuzzy-Weighted Aggregated Sum Product Assessment (WASPAS) method. In the first stage of the presented model, we determined the weight of the criteria by using Pythagorean Fuzzy Critic. In the second stage, we employed Pythagorean Fuzzy Waspas to rank failure modes. A case study was done to identify and evaluate the processes and hazards connected with fighting the COVID-19 virus in healthcare facilities. The use of this integrated approach in healthcare facilities has shown how effective it is at identifying complex risk variables and assisting in well-informed decision-making. Beyond conventional linear models, this integrated approach provides a comprehensive perspective that enables stakeholders to prioritize risks and put actions into place while having an improved understanding of systemic weaknesses. Considering changing worldwide challenges, this research lays the path for resilient and more adaptable risk management methods.